Fullerenes: Characteristics of the substance, biological effects and occupational exposure levels - Anna Maria Świdwińska-Gajewska; Sławomir Czerczak (Nofer Institute of Occupational Medicine, 2016)
Fullerenes are molecules composed of an even number of carbon atoms of a spherical or an ellipsoidal, closed spatial structure. The most common fullerene is the C60 molecule with a spherical structure - a truncated icosahedron, compared to a football. Fullerenes are widely used in the diagnostics and medicine, but also in the electronics and energy industry. Occupational exposure to fullerene may occur during its production. The occupational concentrations of fullerenes reached 0.12-1.2 μ/m3 for nanoparticles fraction (< 100 nm), which may evidence low exposure levels. However, fullerene mostly agglomerates into larger particles. Absorption of fullerene by oral and respiratory routes is low, and it is not absorbed by skin. After intravenous administration, fullerene accumulates mainly in the liver but also in the spleen and the kidneys. In animal experiments there was no irritation or skin sensitization caused by fullerene, and only mild irritation to the eyes. Fullerene induced transient inflammation in the lungs in inhalation studies in rodents. Oral exposure does not lead to major adverse effects. Fullerene was not mutagenic, genotoxic or carcinogenic in experimental research. However, fullerene may cause harmful effects on the mice fetus when administered intraperitoneally or intravenously. Pristine C60 fullerene is characterized by poor absorption and low toxicity, and it does not pose a risk in the occupational environment. The authors of this study are of the opinion that there is no ground for estimating the maximum allowable concentration (NDS) of pristine fullerene C60. Fullerene derivatives, due to different characteristics, require separate analysis in terms of occupational risk assessment. Med Pr 2016;67(3):397-410